Estudo fitoquímico de folhas e polpa de fruto de Maytenus salicifolia (Celastraceae) e análise quimiotaxonômica em Maytenus sp - Frederico Nunes Valladao (2011)
This work describes the chemotaxonomy study of Maytenus salicifolia and Maytenus gonoclada, and the phytochemical study of the fruit pulp and leaves of Maytenus salicifolia colected in UFMG Ecological Station in Belo Horizonte city. The chemotaxonomy study (histochemical and cromatography) makes possible to distinguish the two population of M. salicifolia analyzed and discerned M. gonoclada population from the two groups of M. salicifolia. These results demonstrate that groups assayedexhibit a great ability of adaptation like result of the stresses existant in each habitat which the population worked are inserted. The informations obtained from histochemical techniques, GC/MS and HPLC/UV are critical and fundamental in an eventual adjustment in the taxonomicclassification of the studied species in this work. The phytochemical study made possible to isolate and to identify from M. salicifoliafruit pulp one pentacyclic triterpene lupeol and two flavonoids, rutin and epicatechin. From the leaves of the same plant was possible to identify -amyrin, -amyrin, isomultiflorenol, multiflorenol, epi--amyrin, epi--amyrin, epi-multiflorenol and to isolate the lupeol, -sitosterol, tanacetene as well as three compounds unpublished in scientific literature: 3-araquidoiloxy-11-oxo-ursan-12-ene, 3-esteariloxy-D:C-friedooleanane-7-ene and 1,3-dihydroxy-D:C-friedooleanane-7-ene.